2009
DOI: 10.1038/eye.2009.181
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate outcomes of Ahmed glaucoma valve surgery in Asian patients with intractable glaucoma

Abstract: Objective To evaluate the efficacy and safety of Ahmed glaucoma valve (AGV) implantation in Asian patients with refractory glaucoma. Methods The study was a retrospective interventional case series conducted at a single institution between January 2004 and January 2006. The study population included 91 patients (91 eyes). Results A total of 70 patients were successfully treated (74.5%). Postoperatively, the median intraocular pressures declined significantly to 13 mm Hg (interquartile range: 10-20 mm Hg) on da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…Generalizing the results from these reports to the surgical outcomes of BGI for OAG may be difficult because the surgical outcomes of GDD for refractory glaucoma are quite different from those of BGI for OAG. Among these seven reports, two studies reported opposite results to those in this study; Seah et al 13 and Tai et al 17 have reported that older age was associated with the surgical failure of GDD. In addition to the difference in glaucoma type (OAG and refractory glaucoma), the difference in the age range of patients between the two studies and this study may have caused the difference in the results.…”
Section: Discussioncontrasting
confidence: 76%
“…Generalizing the results from these reports to the surgical outcomes of BGI for OAG may be difficult because the surgical outcomes of GDD for refractory glaucoma are quite different from those of BGI for OAG. Among these seven reports, two studies reported opposite results to those in this study; Seah et al 13 and Tai et al 17 have reported that older age was associated with the surgical failure of GDD. In addition to the difference in glaucoma type (OAG and refractory glaucoma), the difference in the age range of patients between the two studies and this study may have caused the difference in the results.…”
Section: Discussioncontrasting
confidence: 76%
“…Our study differs from other studies that have been mentioned in that the majority of patients who were included in it had chronic angle-closure glaucoma. In general, AGV implantation has been thought to be relatively effective with respect to controlling glaucoma in different types of patients [21], [22], and neither glaucoma nor corneal diagnosis has been shown to influence the success of long-term glaucoma control with GDDs. However, our experience has shown the success rate of AGV implantation may be influenced by the type of glaucoma; for example, we have found evidence of poor outcomes of AGV implantation in controlling neovascular glaucoma [22].…”
Section: Discussionmentioning
confidence: 99%
“…In general, AGV implantation has been thought to be relatively effective with respect to controlling glaucoma in different types of patients [21], [22], and neither glaucoma nor corneal diagnosis has been shown to influence the success of long-term glaucoma control with GDDs. However, our experience has shown the success rate of AGV implantation may be influenced by the type of glaucoma; for example, we have found evidence of poor outcomes of AGV implantation in controlling neovascular glaucoma [22]. Furthermore, our Cox regression analysis also showed that the patients with preexisting angle-closure glaucoma had an increased risk of AGV failure compared with other patients.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the differences in the enrolled populations, follow-up periods, and success criteria, it is difficult to compare success rates across studies. According to previous reports, the complete success rate of AGV implantation has ranged from 25.2% to 94% [ 16 , 17 , 18 ]. Our complete success rate was in accordance with that of the most recent randomized controlled trial by Panos G. Christakis and associates, which compared the AGV with the Baerveldt (AVB) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%